HUBUNGAN PENGETAHUAN, ASI EKSKLUSIF, STATUS EKONOMI DAN POLA ASUH ORANG TUA TERHADAP KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS RONGA–RONGA KABUPATEN BENER MERIAH - Darmi Yulianti; Seri Warzukni; Raodah; Hudnah (LLDIKTI WILAYAH XIII, 2026)
Stunting in toddlers is one of the public health problems that is still a concern in Indonesia. This condition is characterized by non-optimal growth of the child due to chronic malnutrition in the period of the first 1,000 days of life. This study was conducted to analyze the relationship between knowledge, exclusive breastfeeding, economic status, and parenting. Type of quantitative research is cross sectional study design. The population in this study is all toddlers who seek treatment at UPTD Puskesmas Ronga - Ronga. The sample technique used in this study is Purposive sampling. By performing the chi-square test, the results showed that three is a relationship of knowledge to the incidence of stunting (p=0.001 < 0.05), there is a relationship of exclusive breastfeeding to stunting (p=0.000 < 0.05), there is a relationship of economic status to the incidence of stunting (p=0.000 < 0.05), there is a relationship of maternal parenting to the incidence of stunting (p=0.038 > 0.05). thus, it can be concluded that there is a relationship between knowledge, exclusive breastfeeding, economic status, and parenting of parents to the incidence of stunting in UPTD Puskesmas Ronga-Ronga, Bener Meriah. Keywords: Exclusive Breastfeeding, Knowledge, Parenting Style, Economic Status, Stunting